Ti år med norske bildebøker i Polen: Noen betraktninger fra et litteraturformidlingsperspektiv - Tunkiel, Katarzyna A. (Folia Scandinavica Posnaniensia, 2021)
This paper aims to explore how Norwegian picturebooks published in Poland in the years 2008-2018 are presented in publishers' blurbs and adult readers' online reviews. The study is grounded in Scandinavian theory of literature mediation and it makes particular use of the concept of public epitexts. Drawing on research on contemporary Scandinavian picturebooks, the paper identifies the most frequently highlighted aspects of the works discussed in the analysed text corpus. Based on this, the author distinguishes between two strategies of book selection represented among the Polish publishers and attempts to map out an image of the Norwegian picturebooks in the Polish adult audience.